2021
DOI: 10.1080/10942912.2021.1919704
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and enzyme-inhibitory properties of sesame seed protein fractions and their isolate and hydrolyzate

Abstract: Sesame seed was defatted and subsequently fractionated into albumin, globulin, glutelin and prolamin. The defatted flour was also subjected to alkaline solubilization and acid precipitation to obtain protein isolate. The sesame seed protein isolate was hydrolyzed using a combination of pepsin and pancreatin to produce the protein hydrolyzate. The defatted flour, protein fractions, isolate and hydrolyzate were evaluated for their amino acid profiles as well as in vitro antioxidant and enzyme inhibitory activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Unlike most oilseeds, sesame seed protein is rich in sulfur containing amino acids but low in lysine, which makes it a suitable ingredient for supplementing legume proteins (Johnson et al, 1979). A recent report showed that the globulin fraction had the highest level of sulfur containing amino acids at 8.5% when compared to 4.5%, 3.5%, 5.0%, and 4.4% for the albumin, glutelin, prolamin, and the sesame seed protein isolate (SSPI), respectively (Idowu, Famuwagun, et al, 2021). At $15%, the globulin also contained the highest level of arginine when compared to 9%-13% for the other isolated proteins.…”
Section: Sesamementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most oilseeds, sesame seed protein is rich in sulfur containing amino acids but low in lysine, which makes it a suitable ingredient for supplementing legume proteins (Johnson et al, 1979). A recent report showed that the globulin fraction had the highest level of sulfur containing amino acids at 8.5% when compared to 4.5%, 3.5%, 5.0%, and 4.4% for the albumin, glutelin, prolamin, and the sesame seed protein isolate (SSPI), respectively (Idowu, Famuwagun, et al, 2021). At $15%, the globulin also contained the highest level of arginine when compared to 9%-13% for the other isolated proteins.…”
Section: Sesamementioning
confidence: 99%
“…Polypeptide composition of oilseed proteins arise mainly from the four traditional solubility‐based groups, that is, albumin, globulin, prolamin, and glutelin, which are extracted with water, dilute salt solution, aqueous alcohol, and dilute NaOH, respectively (Idowu, Famuwagun, et al, 2021). However, most oilseed proteins are composed essentially of the globulins, which are also sub‐divided into various polypeptide types.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate the potential of food-derived peptides in mitigating oxidative reaction-induced damages in biological and food matrices. A recent study by Idowu et al [76] assessed the sesame seed protein hydrolysate produced using pepsin and pancreatin enzymes for their effective antioxidant potential. The results confirmed that sesame seed protein hydrolysate had the highest hydroxyl radical scavenging and metal chelation activity compared to the unhydrolyzed protein.…”
Section: Antioxidant and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…Tus, providing natural alternatives is of utmost importance. In recent years, characterizing natural antioxidants has received special attention, which leads to studies on antioxidant and antibacterial capacity of peptides derived from hydrolysed proteins of a variety of food resources, e.g., soy protein [2], casein [3], egg white protein [4], seeds of river tamarind [5], sesame seed [6], cowpea [7], Okra seed meal [8], and fsh proteins [9].…”
Section: Introductionmentioning
confidence: 99%